204k views
5 votes
Helpppp fastttt Plz show allll workkkkk​

Helpppp fastttt Plz show allll workkkkk​-example-1

2 Answers

7 votes
Hopefully that helps
User Asterisk
by
6.3k points
3 votes

Answer:


m=8x-5-4\Delta x

Explanation:

We have the function:


f(x)=4x^2-5x-1

And we want to use the difference quotient:


m=(f(x+\Delta x)-f(x))/(\Delta x)

To find the slope function.

So, let's substitute
x+\Delta x for our function. This yields:


m=((4(x+\Delta x)^2-5(x+\Delta x)-1)-(4x^2-5x-1)))/(\Delta x)

Let's square. Use the perfect square trinomial pattern. This yields:


m=((4(x^2+2x\Delta x-\Delta x^2)-5(x+\Delta x)-1)-(4x^2-5x-1)))/(\Delta x)

Distribute:


m=((4x^2+8x\Delta x-4\Delta x^2-5x-5\Delta x-1)-(4x^2-5x-1))/(\Delta x)

Distribute the right:


m=((4x^2+8x\Delta x-4\Delta x^2-5x-5\Delta x-1)+(-4x^2+5x+1))/(\Delta x)

Combine like terms:


m=((4x^2-4x^2)+(-5x+5x)+(1-1)+(8x\Delta x-4\Delta x^2-5\Delta x))/(\Delta x)

The first three terms will cancel. This leaves us with:


m=(8x\Delta x-4\Delta x^2-5\Delta x)/(\Delta x)

We can factor out a Δx from the numerator:


m=(\Delta x(8x-4\Delta x-5))/(\Delta x)

The Δx will cancel. So, our slope function is:


m=8x-5-4\Delta x

And we're done!

User Starkm
by
5.5k points